2009
DOI: 10.3892/ijo_00000299
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of reactive oxygen species and caspase-dependent pathway in berberine-induced cell cycle arrest and apoptosis in C6 rat glioma cells

Abstract: Abstract. The cytotoxicity of berberine on C6 rat glioma cells indicated that berberine induced morphological changes and caused cell death through G2/M arrest and apoptosis. While undergoing apoptosis, there was a remarkable accumulation of G2/M cells with the upregulatoin of Wee1 but it also inhibited cyclin B, CDK1 and Cdc25c that led to G2/M arrest. Along with cytotoxicity in C6 cells, several apoptotic events including mitochondrial cytochrome c release, activation of caspase-9, -3 and -8 and DNA fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…It has also been demonstrated that arsenic tetroxide has a greater potential against human cervix, gastric, and head cancer cells when used in combination 6 , e.g. with paclitaxel 7 . Despite the success of arsenic trioxide in the treatment of APL, its efficacy towards solid tumors is limited by its poor pharmacokinetics and dose-limiting toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that arsenic tetroxide has a greater potential against human cervix, gastric, and head cancer cells when used in combination 6 , e.g. with paclitaxel 7 . Despite the success of arsenic trioxide in the treatment of APL, its efficacy towards solid tumors is limited by its poor pharmacokinetics and dose-limiting toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Both pentavalent and trivalent forms of these arsenic species can be present in urine (20,2225). The trivalent forms of iAs, MMA, and DMA are likely to be the more toxic forms (20,2629) with MMA III having the highest toxicity followed by iAs III (30,31). Previous studies have shown that iAs%, MMA%, and MMA/iAs are positively associated and DMA%, and DMA/MMA are negatively associated with skin lesions with higher levels of MMA% associated with highest risk of skin lesions (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, efficient methylation from inorganic arsenic to DMA is associated with a high rate of arsenic excretion in the urine [6]. Incomplete arsenic metabolism, with higher urinary inorganic arsenic and MMA, but lower DMA, seems to be a marker of increased susceptibility to arsenic-related diseases, including cancer [7], [8].…”
Section: Introductionmentioning
confidence: 99%